The Importance of Digital Education Literacy for Da'wah Students of Islamic Broadcasting Communication - Baihaqi, Mohammad Aqil (Zona Education Indonesia, 2023)
This study aims to describe the importance of digital literacy for students in general, and KPI students in particular. In this modern era, where science and technology are developing so fast. To keep pace with these developments, digital literacy is needed. Digital literacy has an important position in today's all-digital era. Students are also required to master this ability. Through this digital literacy, students will have the ability to find, select and sort information, critically think, be creative, collaborate, and communicate effectively. Therefore, students in the current digital era must have multi-literacy skills that exist in digital literacy including technical abilities, cognitive abilities, and social-emotional abilities. Digital literacy skills possessed by students can be implemented in everyday life, both in the community, family, workplace, and other environments. Included in carrying out da'wah which is the obligation of every Muslim.